How to Seek a Site for Forest Health Care Development—A Case Study in Hainan Tropical Rainforest National Park, China - Ziqi Zheng; Jieling Chu; Guang Fu; Hui Fu; Tao Xu; Shuling Li (Land)
Identifying the most suitable areas for developing forest health care in Hainan Tropical Rainforest National Park (HTRNP) is of great significance to its ecological protection and development. This study selected 107 health care points in HTRNP as research objects to monitor environmental factors, a forest health care evaluation system was constructed based on those environmental factors, and the health care resource points were rated. Kernel density analysis and buffer zone analysis were used to analyze other factors such as roads, villages, and water inside and outside of the national park. Multi-factor superposition analysis of the first-level health care points with other impact factors was performed to obtain a map of the distribution of health care potential in different sub-areas of HTRNP. A total of 67 first-level health care points were selected through the forest health care evaluation system. Through superposition analysis, it was found that, among the seven sub-areas of HTRNP, there are 42 first-level health care points within the 5 km buffer zone for roads and waterways, including 11 in Diaoluo Mountain, 10 in Limu Mountain, 6 in Yingge Ridge, 5 in Jianfeng Ridge, 4 in Bawang Ridge, 4 in Maorui, and 2 in Wuzhi Mountain. There are nine first-level health care points located in the area with a village kernel density greater than 3000, including three in Diaoluo Mountain, two in Limu Mountain, two in Yingge Ridge, and two in Maorui. At the same time, to meet the above two conditions of the first level of health care points, there are six, including three in Diaoluo Mountain, two in Maorui, and one in Yingge Ridge. Through the results analysis, Diaoluo Mountain is considered to be the area with the greatest potential for developing forest health care in HTRNP. In addition, the comprehensive performance of Limu Mountain is second only to Diaoluo Mountain, and Limu Mountain, Maorui, and Yingge Ridge are listed as areas with great potential for developing forest health care.